Eclipse lunar: explicações científicas e míticas de indígenas da etnia Wai Wai - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
How did the Universe come about? What is the origin of the Moon? What explains the formation of eclipses? Questions like these have always been asked and in the most diverse civilizations, but the answers have not always been the same and have not always been in the domain of science. Therefore, the objective of this study is to understand how university indigenous people, of the Wai ethnicity, explain the phenomenon of the lunar eclipse. The Wai-wai ethnicity has its highest territorial population concentration in the municipality of Oriximiná, in western Pará. A questionnaire was used to understand how indigenous students from universities in Western Pará, members of the Wai ethnic community (Mapuera/Trombetas – Oriximiná), explain a certain phenomenon related to the Moon, such as: The lunar eclipse. The results of this questionnaire were organized in a table, making it possible to infer about them in the light of the theoretical framework previously discussed. Some speeches refer us to mythical explanations, as they are presented in fanciful, nonlogical, contradictory ways that reveal a thought that seems to precede critical reflection. However, the explanations about the lunar eclipse, presented by the indigenous people of the Wai ethnic group, are manifested by scientific approaches, but also reveal important aspects of their culture, the influences they suffered, how this community is persuaded to interpret what is one of nature's most beautiful phenomena
Keywords: Eclipse lunar; Etnia Wai Wai; Mitos; CNPQ:: CIÊNCIAS EXATAS E DA TERRA